Announcement of the Stata Journal Editors' Prize 2017. (March 2017) - Newton, H. Joseph; Cox, Nicholas J.
The editors of the Stata Journal are pleased to invite nominations for their 2017 prize in accordance with the following rules. Nominations should be sent as private email to editors@stata-journal.com by July 31, 2017.